ChemInform Abstract: Palladium‐Catalyzed 1, 4‐Addition of Terminal Alkynes to Acrolein. Issue 51 (December 2015) - Wang, Haining; Hearne, Zoe; Knauber, Thomas; Dalko, Maria; Hitce, Julien; Marat, Xavier; Moreau, Magali; Li, Chao‐Jun
Abstract: The scalable title transformation of arylalkynes in acetone provides the corresponding 4‐alkynals in moderate to often high yields whereas application of water as the solvent delivers the products in moderate yields.